Mapping Our World: An Introduction to the Art of Cartography - (:unkn) unknown (My University, 2023)
As long as people have existed, maps have served an important purpose as a teaching tool, helping us organize knowledge and understand our world. In this six-lesson cartography unit, students view and engage with maps from the American Geographic Society Library’s collection. They are introduced to cartography, explore a variety of artistic media and techniques, and investigate what maps can tell us about the people who made them.